Water Level Monitoring and Flood Early Warning Using Microcontroller With IoT Based Ultrasonic Sensor - Agus Diriyana; Ucuk Darusalam; Novi Dian Natasha (Institute of Computer Science (IOCS), 2019)
In recent years, floods Often result in material, financial and even loss of life. The absence of an early warning system when floods occur makes people less aware of the occurrence of floods. In this study, Researchers designed a flood detection system that works automatically to monitor water levels and send an early flood warnings. This water level monitoring system uses the nodemcu esp8266 with ultrasonic sensors and based on IOT to provide real-time the data to find out the water level created at Certain levels. This system is connected online that displays real-time water level data on the thingspeak platform and is integrated with the telegram application as a flood early warning. The results of the test of this system design have accuracy of ultrasonic sensors on the which produce an average error rate of 0.78% and an average error of 1 cm.